Analysis of The Economic Influence of Society on Economic Independence In Balumbung Village Tompobulu Sub-District, Bantaeng Regency - Abdul Rahman (Pelopor Publikasi Akademika, 2023)
Analysis of the economic impact of residents on economic independence in Balumbung Hamlet, Tompobulu District, Bantaeng Regency. This research intends to analyze the economic contribution of citizens to economic independence in Balumbung Hamlet, Tompobulu District, Bantaeng Regency and analyze economic independence in Balumbung Hamlet, Tompobulu District, Bantaeng Regency. Information collection is carried out by monitoring, questioning and selecting Information analysis using the form of Miles and Huberman is the reduction of information, presentation of information and conclusions or verification. The results of the research prove that together when connected freely elastic with elastic tied to good elastic income levels, expenditure for food in fact has an important bond in a small degree. Elastic is tied to expenditure on food, either partially or jointly influenced by income and family body size has an important effect on non-food expenditure Elastic income level is jointly influenced in an important way by free communication payments so that greatly influences. Another thing is when connected elastically tied to the level of income and the freedom of communication fees.